Five Frames for the Decameron : Communication and Social Systems in the CORNICE - Potter, Joy Hambuechen (Book collections on Project MUSE., 2014)
Using a fourfold approach derived from symbolic anthropology, sociology, semiotics, and philology, Joy Hambuechen Potter focuses on the cornice, or frame tale, of the Decameron, its purpose, and its relationship to the stories. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions.